PEMANFAATAN SAAS UNTUK STRATEGI PEMASARAN DIGITAL PADA UMKM: STUDI KASUS CV GEMILANG KENCANA - Adiana, Beta Estri; Mareta, Affix (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This research aims to analyze the utilization of Canva as a Software as a Service (SaaS) platform in supporting digital marketing strategies for Micro, Small, and Medium Enterprises (MSMEs). A case study was conducted on CV Gemilang Kencana, a traditional food-processing MSME based in Wonosobo Regency. The research employed a qualitative descriptive method using data collection techniques such as direct observation of Instagram content, semi-structured interviews with the business owner, and documentation of visual promotional materials. The findings reveal that Canva accelerates the content design process, maintains brand visual consistency, and enhances audience engagement. One post designed using Canva reached up to 1,562 accounts and gained 1,900 impressions, with more than 60% coming from non-followers. Moreover, visual strategies such as customer testimonials and local tourism narratives effectively foster emotional connections with consumers. However, limitations such as restricted features in the free version and low design literacy remain challenges. Overall, Canva proves to be a strategic tool for efficient and effective digital branding among MSMEs.